An Act Incorporating the City of Cincinnati: And a Digest of the Ordinances of Said City, at 57-58, An Ordinance to Regulate the Keeping of Gunpowder, § 1 (1835) - (:unkn) unknown (My University, 1835)
That no person or persons in the city of Cincinnati, shall keep, have, or possess, in any house, warehouse, shop, shed, or other building, nor in any street, side walk, lane, alley, passage, way, or yard, nor in any cellar, wagon, cary, or carriage, of any kind whatever; nor in any other place, within said city, Gun Powder, in any way or manner, other than as provided for by this ordinance; nor in any quantity exceeding twenty-five pounds, to be divided into six equal parts. § 2. Be it further ordained, That it shall not be lawful for any person or persons to sell gun powder by retail within said city, without having first obtained a license from the city council for that purpose; and every person obtaining a grant for a license to sell gun powder, shall receive a certificate of such grant from the city clerk, and pay into the city treasury, a sum not exceeding one hundred dollars, nor less than ten dollars
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER